Molecular profile of BRCA-mutated biliary tract cancers. Issue 3 (23rd June 2020) - Spizzo, Gilbert; Puccini, Alberto; Xiu, Joanne; Goldberg, Richard M; Grothey, Axel; Shields, Anthony F; Arora, Sukeshi Patel; Khushman, Moh'd; Salem, Mohamed E; Battaglin, Francesca; Baca, Yasmine; El-Deiry, Wafik S; et al.
Abstract : Introduction: Prognosis of biliary tract cancers (BTC) remains dismal and novel treatment strategies are needed to improve survival. BRCA mutations are known to occur in BTC but their frequency and the molecular landscape in which they are observed in distinct sites of BTC remain unknown. Material and methods: Tumour samples from 1292 patients with BTC, comprising intrahepatic cholangiocarcinoma (IHC, n=746), extrahepatic cholangiocarcinoma (EHC, n=189) and gallbladder cancer (GBC, n=353), were analysed using next-generation sequencing (NGS). Tumour mutational burden (TMB) was calculated based on somatic non-synonymous missense mutations. Determination of tumour mismatch repair (MMR) or microsatellite instability (MSI) status was done by fragment analysis, immunohistochemistry and the evaluation of known microsatellite loci by NGS. Programmed death ligand 1 expression was analysed using immunohistochemistry. Results: Overall, BRCA mutations were detected in 3.6% (n=46) of samples ( BRCA1: 0.6%, BRCA2: 3%) with no significant difference in frequency observed based on tumour site. In GBC and IHC, BRCA2 mutations (4.0% and 2.7%) were more frequent than BRCA1 (0.3% and 0.4%, p<0.05) while in EHC, similar frequency was observed (2.6% for BRCA2 vs 2.1% for BRCA1 ). BRCA mutations were associated with a higher rate in subjects with MSI-H/deficient mismatch repair (19.5% vs 1.7%, p<0.0001) and tumours with higher TMB, regardless of the MMR or MSI status (p<0.05). Conclusions: BRCA mutations are found in a subgroup of patients with BTC and are characterised by a distinct molecular profile. These data provide a rationale testing poly(ADP-ribose)polymeraseinhibitors and other targeted therapies in patients with BRCA -mutant BTC.